A Trust Management Model for IoT - Abdlrazaq, Ahmed; Varol, Serkan (Ieee, 2019)
The Internet of Things (IoT) is profoundly influencing our daily lives in many areas, covering small devices to large network systems. An IoT system may be a set of directing rules that rearranges the usage of IoT applications. This paper details a trust management model and security of IoT systems. Trust management models and security play a critical part in IoT to protect information and devices from attacks since it supplies security for all layers and networks. This review focuses on how a trust management model has a significant function in IoT in enhancing reliability, privacy, and security. In this survey, we explained the challenges along with the solutions in terms of IoT security and privacy and recognized the main security problem in the IoT framework. In addition, this paper explored the characteristics of trust and pointed out some IoT security challenges, explaining how middleware can affect the security of IoT.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Internet of Things (IoT); Trust Management Model (TMM)